2015
DOI: 10.1590/0004-282x20150117
|View full text |Cite
|
Sign up to set email alerts
|

Patients with multiple sclerosis do not necessarily consume more alcohol or tobacco than the general population

Abstract: Purpose Recent papers suggest that patients with multiple sclerosis (MS) are prone to alcohol misuse. This may be due to the combination of a lifelong and disabling disease with a psychiatric profile typical of MS. The objective of the present study was to assess these findings in a culturally different population of patients with MS.Method The present case-control transversal study assessed 168 patients with MS and 168 control subjects from Brazil.Results There were no evidence that patients with MS drank mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…From reading titles and abstracts, 312 papers did not fulfil the specified criteria and, therefore, 30 papers were initially selected for full consideration. In the end, eleven research articles published between 2004 and 2016 were included in this review [8][9][10][11][12][13][14][15][16][17][18]. Papers discussing the role of lifestyle habits in relation to MS were typically very recent publications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From reading titles and abstracts, 312 papers did not fulfil the specified criteria and, therefore, 30 papers were initially selected for full consideration. In the end, eleven research articles published between 2004 and 2016 were included in this review [8][9][10][11][12][13][14][15][16][17][18]. Papers discussing the role of lifestyle habits in relation to MS were typically very recent publications.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the data from these papers is shown in Table 1 The results from these studies were not uniform. For example, the rate of excessive alcohol consumption by patients with MS ranged from 3% [18] to 40% [15]. Two studies showed an inverse relationship between the habit of drinking alcohol and the progression of disability in MS [12,16].…”
Section: Resultsmentioning
confidence: 99%